Creation of an enabling environment for improved land tenure reform in Uganda - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
Increased knowledge and understanding of the importance of tenure reform among NGOs, forest adjacent communities and technocrats. National stakeholders credited the project with being the main influence on how the gendered implications of forest tenure reform were understood nationally.